Positive and negative effects of the minimum wage subsidy, through oversight, in the labor market - Sánchez Cortazar, Diego (Revista Internacional de Salarios Dignos, 2025)
The article analyzes fiscal strategies, addressing the topic of the federal revenue and expenditure budget, highlighting its importance for the country's monetary collection, as well as the way the State obtains income to meet national needs. In particular, one of the population’s key needs is to achieve better income and purchasing power to meet their demands, such as acquiring a basic and dignified basket of goods. The main objective of this study is to analyze the effects of the minimum wage subsidy, financed through tax collection and fiscal oversight, on employment and informality in the Mexican labor market. Likewise, it examines the labor policy aimed at increasing minimum wages, which the State has established as a priority, a policy supported by tax revenue, and discusses its effects on the labor market. Specifically, if the State decides to raise the minimum wage and finances it through tax collection, companies may have more capacity to create jobs. Methodologically, a two-stage least squares regression model is used, based on labor market variables such as tax revenue, minimum wage, unemployment, and number of informal businesses. However, if the State enforces a very strict tax policy to support higher wages, this approach may lead companies to choose informality instead. The main results show that while tax revenue can support minimum wage increases and help reduce unemployment, it also leads to an increase in informal businesses. It is therefore proposed that effective oversight must be accompanied by support programs and tax education policies to avoid adverse effects such as informality and to foster a better perception of fiscal policy among taxpayers.